Clinical and pathological evaluation of benign skin lesions - Destek, Sabahattin; Gul, Vahit Onur (Penerbit Universiti Kebangsaan Malaysia, 2019)
Skin lesions are commonly benign in nature. The present study aims to evaluate the prevalence and clinicopathological characteristics of a large series of benign skin lesions (BSLs) excised in our clinic. Patients with skin lesions who underwent total excisional biopsy at the general surgery clinic between 2012 and 2016 were reviewed. A total of 551 patients with BSLs were included in the study. Of these, 43.7% were females and 56.7% were males. The age range was between 2 and 98 years with a mean of 39.7 years. The most commonly occurring group of BSLs was of the appendageal tumors (33.3%), and this finding was statistically significant. The most common keratinocytic BSL (13.6%) was verruca vulgaris. In the present study, various types of BSLs and their occurrences were evaluated. Benign skin tumors can turn into malignant types. A biopsy should be performed to establish the exact diagnosis. We performed an excisional biopsy to confirm the diagnosis.